1970
DOI: 10.3126/jnps.v28i2.1387
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum and Outcome of Empyema in Nepalese Children

Abstract: Keywords: Empyema; chest tube drainage, decorticationDOI = 10.3126/jnps.v28i2.1387J. Nepal Paediatr. Soc. Vol.28(2) 2008 p.49-51

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A previous study from our institute showed that almost 18% of patients with empyema thoracis failed conservative management with tube thoracostomy, and required surgical intervention. 7 However, there was then no dedicated thoracic surgery at our centre and most children were managed elsewhere up to 2016. There are few data on the clinical profile and outcomes of surgical intervention for late-stage empyema thoracis in children in our population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study from our institute showed that almost 18% of patients with empyema thoracis failed conservative management with tube thoracostomy, and required surgical intervention. 7 However, there was then no dedicated thoracic surgery at our centre and most children were managed elsewhere up to 2016. There are few data on the clinical profile and outcomes of surgical intervention for late-stage empyema thoracis in children in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Natural orifice transluminal endoscopic surgery (NOTES) has been predicted to replace conventional laparoscopy in the near future. [1][2][3][4][5][6][7][8][9][10] In addition, the transvaginal route, having typical physical and physiological benefits, [1][2][3][4][5][6][11][12][13][14][15][16] makes it the safest, as well as an immensely popular method. [1][2][3]6,[11][12][13][14][15][17][18][19][20][21][22][23][24][25][26] However, even a decade after its inception, it continues to be fraught with diverse technical hurdles such as spatial constraints, inadvertent vaginal gas-leak, compelling requirements for complex instrumentation, scarce availability and affordability, and a steep learning curve, to name a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation